Physical properties and H-ionizing-photon production rates of extreme nearby star-forming regions. Issue 3 (15th June 2018) - Chevallard, Jacopo; Charlot, Stéphane; Senchyna, Peter; Stark, Daniel P; Vidal-García, Alba; Feltre, Anna; Gutkin, Julia; Jones, Tucker; Mainali, Ramesh; Wofford, Aida
ABSTRACT: Measurements of the galaxy UV luminosity function at z ≳ 6 suggest that young stars hosted in low-mass star-forming galaxies produced the bulk of hydrogen-ionizing photons necessary to reionize the intergalactic medium (IGM) by redshift z ∼ 6. Whether star-forming galaxies dominated cosmic reionization, however, also depends on their stellar populations and interstellar medium properties, which set, among other things, the production rate of H-ionizing photons, ξ_ion^, and the fraction of these escaping into the IGM. Given the difficulty of constraining with existing observatories the physical properties of z ≳ 6 galaxies, in this work we focus on a sample of 10 nearby objects showing UV spectral features comparable to those observed at z ≳ 6. We use the new-generation beagle tool to model the UV-to-optical photometry and UV/optical emission lines of these local 'analogues' of high-redshift galaxies, finding that our relatively simple, yet fully self-consistent, physical model can successfully reproduce the different observables considered. Our galaxies span a broad range of metallicities and are characterized by high ionization parameters, low dust attenuation, and very young stellar populations. Through our analysis, we derive a novel diagnostic of the production rate of H-ionizing photons per unit UV luminosity, ξ_ion^, based on the equivalent width of the bright [O iii ] λ λ 4959, \!5007 line doublet, which does not require measurements of H-recombination lines. This new diagnostic can be used to estimate ξ_ion^ from future direct measurements of the [O iii ] λ λ 4959, \!5007 line using JWST /NIRSpec (out to z ∼ 9.5), and by exploiting the contamination by H, β +[O III] λ λ 4959, \! 5007 of photometric observations of distant galaxies, for instance from existing Spitzer /IRAC data and from future ones with JWST /NIRCam.